2008
DOI: 10.1111/j.1399-0012.2008.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow reserve dysfunction in hemodialysis and kidney transplant patients

Abstract: Renal transplant and HD patients had lower CFR values detected by TTDE, which may be regarded as an early finding of an affected cardiovascular system. CFR is more impaired in HD patients than renal transplant recipients. Uremia-associated microvascular disease may be responsible for CFR impairment in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 28 publications
(38 reference statements)
3
24
3
Order By: Relevance
“…By using this method, early coronary microvasculature pathology and ED can be investigated [6,7]. Decreased CFR values (CFR <2) reflect coronary ED and may be evidence of severe coronary artery disease [6,7,8,9]. In our previous study, we have also demonstrated that impaired CFR was significant in PD patients [10].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…By using this method, early coronary microvasculature pathology and ED can be investigated [6,7]. Decreased CFR values (CFR <2) reflect coronary ED and may be evidence of severe coronary artery disease [6,7,8,9]. In our previous study, we have also demonstrated that impaired CFR was significant in PD patients [10].…”
Section: Introductionmentioning
confidence: 93%
“…The CFR measurement which reflects coronary microvascular function and endothelial functions of epicardial coronary arteries by TTDE, as a cheaper and easy screening test, may be used as a detection method in the assessment of major epicardial coronary arteries [7,8,9,10]. Impairment of the CFR (CFR <2) has been suggested to be a preclinical sign of CV events and is characterized by a decreased capacity of the coronary dilatation following an increase in myocardial metabolic demands [7,8,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] In a recent study, decreased CFR values were detected in 89.6% and 59.3% of HD and renal transplant patients, respectively. [22] However, in this study, decreased CFR values were noted in 14 of 24 (58.3%) patients. This is the first study to provide data of CFR values in PD patients.…”
Section: Discussionmentioning
confidence: 46%
“…This may be the reason for the low rate of PD patients with decreased CFR values compared to HD or renal transplant patients in the previous studies. [22] Many well-defined CV risk factors that may affect coronary microvascular and endothelial functions in PD patients, including age, gender, smoking status, BMI, blood pressure, and cholesterol levels, were similar in the low CFR and high CFR groups. We therefore studied ghrelin and leptin levels as new CV risk factors.…”
Section: Discussionmentioning
confidence: 99%